MENUMBUHKAN JIWA KEMANDIRIAN SISWA DAN MENINGKATKAN KUALITAS LINGKUNGAN HIDUP MELALUI TANAMAN HIDROPONIK - Edy Sukoco (EduStream: Jurnal Pendidikan Dasar, 2022)
The background of this best practice is that the students' self-reliance spirit has not yet developed optimally. If a situation like this is not handled immediately, it is feared that it will affect student achievement in school. Therefore, life skills-oriented education is an alternative prospective educational reform to anticipate future demands. One of life skills-oriented education is hydroponic management. hydroponic management in schools as a way to increase the spirit of independence of students at SDN Dukuh Menanggal I Surabaya. By using a check list instrument at the time of observation/observation on students after students are given the responsibility to care for hydroponic plants, the development of students' independence after hydroponic management will be known. From the monitoring results, it was concluded that the students' self-reliance as indicated by five indicators included: student attendance, homework collection, self-initiative, self-confidence and responsibility had increased. From 6.96 in the less category (attached calculation) before the implementation, it increased to 14.25 or included in the good category.